CHIP: collaborative host identity protocol with efficient key establishment for constrained devices in Internet of Things - Porambage, P; Braeken, A; Kumar, P; Gurtov, A; Ylianttila, M (Springer US, 2017)
The Internet of Things (IoT) is the next evolutionary paradigm of networking technologies that interconnects almost all the smart objects and intelligent sensors related to human activities, machineries, and environment. IoT technologies and Internet Protocol connectivity enable wide ranges of network devices to communicate irrespective of their resource capabilities and local networks. In order to provide seamless connectivity and interoperability, it is notable to maintain secure end-to-end (E2E) communication links in IoT. However, device constraints and the dynamic link creations make it challenging to use pre-shared keys for every secure E2E communication scenario in IoT. Variants of Host Identity Protocol (HIP) are adopted for constructing dynamic and secure E2E connections among the heterogeneous network devices with imbalanced resource profiles and less or no previous knowledge about each other. We propose a solution called collaborative HIP (CHIP) with an efficient key establishment component for the high resource-constrained devices in IoT. CHIP delegates the expensive cryptographic operations to the resource rich devices in the local networks. Finally, by providing quantitative performance evaluation and descriptive security analysis, we demonstrate the applicability of the key establishment in CHIP for the constrained IoT devices rather than the existing HIP variants.